Effectiveness of Two Different Irrigants - SmearClear and Q-Mix in Removal of Smear Layer: A Comparative Scanning Electron Microscope Study - Ankit Sharma; Divya Mishra; Akshada Mungee; Sabyasachi Chakraborty; Sumit K. Khatore; Namrata Mishra (Journal of Pharmacy and Bioallied Sciences)
Aim: To evaluate and compare the smear layer removal capabilities of Smear Clear and Q-Mix using scanning electron microscopy. Materials and Methods: Forty-two human premolars were standardized to a 10 mm root length, cleaned, and shaped with X2 universal rotary ProTaper. The samples were divided into two groups for final irrigation: Group 1 with 17% Ethylene diamine tetra acetic acid (EDTA) (n = 20) and Group 2 with Q-Mix (n = 20). The canals were sectioned and analyzed under an SEM at various root levels. Statistical analysis was performed at a significant level of 0.05. Result: QMix performed better at removing the smear layer than Smear Clear. Conclusion: QMix, a newly introduced irrigant, effectively removed the smear layer from the apical region of the root canal, which is typically inaccessible to conventional irrigants.